The Political Dimension in Arab Contemporary Art through the Marcuse Aesthetic Theory: A Descriptive Analytical Study - Rafee, Y.M (Department of Medical Science, Neither University, Neitherland, 2019)
This paper discusses the political dimension in Arab contemporary art based on the Marcuse aesthetic theory. The researchers believe there is a high correlation between Arab contemporary art and Marcuse aesthetic theory when the three main axes of this theory are tested and reflected on contemporary Arab artworks (study sample). This study attempts to describe and analyze the artworks (study sample) and link this analysis to Marcuse theory. The study sample contains three Arab contemporary artworks from 2010-2015 to clarify the political dimension in Arab contemporary art in accordance with the Marcuse aesthetic theory. The findings prove strong correlations between Arab contemporary art and Marcuse aesthetic theory.